Prospects for Interest-Free Micro Finance in India: An Empirical Study - Irfan Ahmed Sheikh (Journal of Islamic Economic and Business Research, 2021)
Despite the growth of Islamic banking and finance, in recent times due attention were given to the issue of Islamic microfinance. It is so because, as per various estimates over two billion people across globe are still living in a miserable poverty which is a global challenge and India not being an exception. Since the Poverty remains, a continuous challenge throughout the human history so as the efforts to overcome poverty. Among various efforts a conventional micro finance a â€œnew modelâ€ received global recognition and a hope. But even if successful stories in bringing development and eradicating poverty by small credit tool to poor and by gaining growing attentions by world bank , still millennium development goal remains unachieved. The criticsâ€™ remains not only restricted to, in reaching all forms of poor rather high unbearable interest rates and avoidance by Muslims due to interest are on debate. As an alternative, Islamic finance has its operations both in Islamic and Non-Islamic countries along Islamic Micro finance. It is so because Islamic microfinance programs are complement to Islamic banking, both in ideological and in practical terms. Although IMF is still in infancy stage even though growing rapidly. Various experiments either on individual level or group level are mostly practicing Islamic micro credit products. But Islamic micro crediting has not been yet formally reached to people for India. Therefore this study aims to investigate the prospects based on determinants. The target population has been taken a potential benifacries of interest free micro finance. The paper adopts a Quantifiable approach as a Questionnaire distributed in paper format based on stratified sampling with 602 as final responses. The findings shows that in general the community is cognizant of the various terms used in Interest free microfinance but in respects of products/services existing by Islamic microfinance institutes, it indicates the level of awareness is very low.